Integrating gender into livestock projects is crucial to sustainable successful rural development - Mattioli, R. (International Livestock Research Institute, 2012)
In November 2011, Raffaele Mattioli (Food and Agriculture Organization Animal Production and Health Division) participated in a training workshop on integrating gender in livestock projects and programs for FAO country livestock officers and partners in East and Southern Africa. Here he reflects on the workshop activities and outcomes.